THE MISUNDERSTOOD PERCEPTION IN PRONOUNCING ENGLISH WORDS - Noviana Riahilary; Yussi Mutia PS; Harum Natasha (Institut Agama Islam Negeri Padangsidimpuan, 2016)
Psycholinguistics sides of a language seems to be interesting to be investigated. Thus, this research was aimed at knowing “How students’ misunderstood perception in pronouncing English words”. Research method is being used in this research is quantitative method. Afterwards this research is described in systematic, factual and accurate about facts or certain object characteristic. This research is executed for 3 weeks: April 28-May 11 2016. The research was conducted at State Islamic University of Sultan Syarif Kasim Riau. The population of the research was all of the students in English Education Department VI I Class with the total number of 25. Then, in determining the sample the researchers took 10 people by using random sampling. The total number of the sample was 10 students. The instrument used was a questionnaire to measure the students’ perception in pronouncing English words that consists of ten questions. The main findings show that most of students have misunderstanding about meaning in English communication.